THE IMPACT OF CORE STABILITY EXERCISE WITH THE NEW BOBATH CONCEPT METHOD ON POST-STROKE PATIENT BALANCE AT RSPAL DR RAMELAN SURABAYA - Iqbal, Mohammad; Perdana, Suryo Saputra; Prasetyo, Dedi (Academic Physiotherapy Conference Proceeding, 2021)
Aim: This research aim to know therapeutic exercise appplication with New Bobath Concept approach combining with Core Stability Exercise to improve balance. Quasi experimental design A-B-A use 2 samples measuring every series at a control grup ar RSPAL Dr Ramelan Surabaya. Data analysis with simple descriptive statistic to get obvious image about intervention outcome, using line graphic as an interpretation of treatment and outcome. Based on the grapic shows there is improvement after Core Stability Exercise and New Bobath Concept approach get improvement in 2 items in first week and 2 items in third week. In second week only 1 item get improvement. Conclusion is there is improvement effect in balance by treatment Core Stability Exercise and New Bobath Concept approach.